Promosi Kesehatan Menggunakan Aplikasi Whatsapp untuk Meningkatkan Kepatuhan Minum Tablet Tambah Darah Pada Remaja Putri di Masa Pandemi Covid-19 - Riyanto, Agus (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2021)
Anemia incidence is a female reproductive health problem, if a female is anemia, it is dangerous during pregnancy and childbirth. Female teens in Indonesia in 2019 there were 10.3% received blood supplement tablets and in West Java only 8.2%. The purpose of this study is to examine the effectiveness of Health promotion using whatsapp application to improve taking blood supplement tablets adherence of female teens during pandemic Covid-19. This study is a non-equivalent control group design. Selected the control and intervention groups from female teens Madrasah Aliyah Negeri (MAN) in Cimahi. Samples consisted of 54 female teens; 27 as control and 27 as intervention groups. This study was conducted for three months, the intervention group was given health promotion of taking blood supplement tablets using whatsApp application once a week within 30-60 minutes duration. The assessment of knowledge, attitudes, and adherence of female teens was assessed three times within three month using a questionnaire on google form. Statistical analysis used were independent t test and Mann Whitney test. The results showed that the knowledge of female teens between the control and intervention groups before the intervention and after the one month intervention was no significant difference (p>0.05), while after the three-month intervention there was a significant difference (p<0.05). There was no significant difference between the attitude and adherence of female teens to taking blood supplement tablets between the control and intervention groups before the intervention (p>0.05), where was after the onemonth intervention and after the three-month intervention there was a significant difference (p< 0.05). Suggest the schools work together with health centers and universities to provide health promotions about blood supplement tablets regularly using application media such as whatsapp